AB0727 WORK OUTCOMES AND ASSOCIATED FACTORS IN ANKYLOSING SPONDYLITIS PATIENTS IN CHINA. (2nd June 2020) - Tu, L.; Xie, Y.; Lv, Q.; Yang, M.; Liao, Z.; Cao, S.; Wei, Q.; Gu, J.
Abstract : Background: Poorer work productivity due to pain and functional impairment is commonly seen in ankylosing spondylitis (AS) patients, which may contribute to huge social economic burden. However, data about work outcomes and associated factors in Chinese AS patients were barely reported. Objectives: To assess work outcomes and identify factors associated with poor work productivity in patients with AS in China. Methods: A cross-sectional study was conducted in China. Adult patients (aged ≥ 18 years) fulfilled the 1984 New York modified criteria of AS were enrolled from rheumatology center from Jan 2017 to Aug 2017. All participants completed questionnaires about socio-demographic characteristics, disease characteristics, quality of life and the Work productivity and activity impairment questionnaire in AS (WPAI:SpA) to accesses the impact of chronic health conditions on job performance and productivity. Factors associated with work outcomes were evaluated. Results: A total of 91 patients with AS were included: 87.8% males, 78.02% employed, mean age and disease duration of 30 and 10 years respectively. The mean (SD) activity impairment of all patients was 48.57% (22.02%). For patients with employed work, mean (SD) absenteeism, presenteeism and work productivity loss were 10.22% (19.44%), 43.86% (22.48%) and 47.92% (25.81%) respectively. In multivariable analysis, activity impairment was associated with Bath Ankylosing Spondylitis Functional Index (BASFI) ( P <0.01) and Ankylosing Spondylitis Quality of Life (ASQoL) ( P <0.01). Absenteeism was associated with disease duration ( P =0.03). Presenteeism was associated with disease duration ( P =0.04), BASFI ( P <0.01) and ASQoL ( P <0.01). Work productivity loss was associated with BASFI ( P <0.01) and ASQoL ( P <0.01). Conclusion: Longer disease duration, reduced physical function and poorer quality of life are associated with reduced work productivity in Chinese AS patients. References: [1]Boonen A, van der Heijde D, Landewe R, Spoorenberg A, Schouten H, Rutten-van Molken M, et al. Work status and productivity costs due to ankylosing spondylitis: comparison of three European countries. Annals of the rheumatic diseases. 2002;61(5):429-37. [2]Martindale J, Shukla R, Goodacre J. The impact of ankylosing spondylitis/axial spondyloarthritis on work productivity. Best Pract Res Clin Rheumatol. 2015;29(3):512-23. [3]Castillo-Ortiz JD, Ramiro S, Landewe R, van der Heijde D, Dougados M, van den Bosch F, et al. Work Outcome in Patients With Ankylosing Spondylitis: Results From a 12-Year Followup of an International Study. Arthritis Care Res (Hoboken). 2016;68(4):544-52. [4]Sag S, Nas K, Sag MS, Tekeoglu I, Kamanli A. Relationship of work disability between the disease activity, depression and quality of life in patients with ankylosing spondylitis. J Back Musculoskelet Rehabil. 2018;31(3):499-505. [5]Goh Y, Kwan YH, Leung YY, Fong W, Cheung PP. A cross-sectional study on factors associated with poor work outcomes in patients with axial spondyloarthritis in Singapore. Int J Rheum Dis. 2019;22(11):2001-8. Disclosure of Interests: None declared